Improving Students’ English Skill through Teaching Literature as its Unique Discourse - Suatmo Pantja Putra (Universitas Merdeka Malang, 2016)
This study presents an analysis of the teaching literature. Approaches to literature teaching seem to be much influenced by current approaches to both language and education. There seems, however, to be a tendency to treat literature as merely another subject on the curriculum. Such a tendency has ultimately led to the neglect of features which mark literature as a discourse and an area of study demanding different techniques of description and different pedagogical approaches. Further, it is often assumed that principles formulated for education in general, or for the teaching of foreign languages in particular, can be extended unchanged to the literature class, on the assumptions that it is a subject of the curriculum and an instance of language use. Yet, it may not be the real case. Social uses of language demand rapid response and intensive interaction. Therefore, in teaching of a foreign language, there are good reasons to encourage constant student interaction and reaction toward their engagement in literary world.